2019
DOI: 10.5765/jkacap.190014
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Self-Mutilation in Adolescence Based on the Theory of Mentalization: From Sukhvinder in the Novel ‘Casual Vacancy’

Abstract: Objectives: Adolescence involves a number of developmental processes, as well as unique psychological characteristics and behaviors. An increased rate of internet and game addictions, school violence, and suicide may either represent aspects of adolescence or a psychopathological phenomenon. There is an urgent need to develop software programs that can prevent and resolve adolescent behavioral problems. We applied the mentalization theory to interpret and find solutions for problems faced by adolescent charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For Krystal, more mature ego development could progress as she received genuine support from Mr Fairbrother and experienced empathy and affection through group activities. Krystal used to tease Sukhvinder, but as Mr Fairbrother appropriately pointed out the problems of such behaviour, she could finally see the consequences of her actions for others and experience the painful but precious emotions to help her reflect on herself [ 8 ]. However, the gradual development of Krystal’s identity was disturbed abruptly by the sudden death of Mr Fairbrother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Krystal, more mature ego development could progress as she received genuine support from Mr Fairbrother and experienced empathy and affection through group activities. Krystal used to tease Sukhvinder, but as Mr Fairbrother appropriately pointed out the problems of such behaviour, she could finally see the consequences of her actions for others and experience the painful but precious emotions to help her reflect on herself [ 8 ]. However, the gradual development of Krystal’s identity was disturbed abruptly by the sudden death of Mr Fairbrother.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome such limitations in practice, the authors of this study had previously conducted an investigation on a literary work to analyse the characters and form hypotheses to excavate the necessary data [ 8 ]. In the present study, the case of the suicide of the character Krystal in the novel The Casual Vacancy by Joanne Rowling [ 9 ] was analysed in lieu of an actual adolescent suicide case, so as to determine the factors associated with increased risk and protective effect for adolescent suicide.…”
Section: Introductionmentioning
confidence: 99%
“…and unstable attachment, were associated with selfharm in later life [1,2]. Community-based study also reported that poor family function mediates the association between childhood adversity and nonsuicidal self-injury (NSSI) in adolescence [3].…”
mentioning
confidence: 99%